Editor's Introduction - Conlan, Chris (API Network, 2004)
As practising (or about-to-practise) ESL teachers, we clearly have a comprehensive working knowledge of our subject matter; and it is as a direct result of this knowledge (when yoked to our practical understandings of the construction of Australian social reality) that we are able to make sense of such diverse (but quite authentic) examples of language usage.